Living Qur'an Through Calligraphy Extracurricular (Living Qur’an Melalui Ekstrakurikuler Kaligrafi) - Mandasari, Dayanti; Arsyad, Junaidi (Shautut Tarbiyah, 2024)
This research is motivated by students who take part in calligraphy extracurricular activities at MAS PTPN VI Berangir, where calligraphy, as an art form with Qur'anic values, has been made an extracurricular activity. The purpose of this study is to examine the impact of calligraphy extracurricular activities on students in practising Qur'anic values, known as the concept of Living Qur'an. This study uses a qualitative method with a descriptive analysis approach. The research location was at MAS PTPN VI Berangir, North Labuhanbatu Regency, with data sources obtained from interviews with calligraphy extracurricular teaching teachers, as well as observation and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The results showed that the process of implementing Living Qur'an was divided into two, namely the learning process and the understanding process. The impact of Living Qur'an through this calligraphy extracurricular is that students become more appreciative of the Qur'an and take the time to read the Qur'an after fard prayers, where those who were previously lazy to read it are now diligent. The challenges faced in this Living Qur'an process include an unsupportive social environment as well as students' lack of motivation and laziness. Keywords: Living Qur'an, Extracurricular, Calligraphy